Low-sulfur activated carbon and preparation method thereof

Through the coordinated catalytic and activation of hydrogen and water vapor, the problems of high sulfur content and small mesoporous volume of activated carbon are solved, and the preparation of low-sulfur activated carbon is realized, the surface area and pore structure of activated carbon is improved, and production costs and resource waste are reduced. .

CN119306219AActive Publication Date: 2025-01-14CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202310867312.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-14
Publication Date
2025-01-14
Estimated Expiration
2043-07-14

AI Technical Summary

Technical Problem

The existing activated carbon has high sulfur content and small mesoporous volume, making it difficult to meet the needs of catalytic reactions. At the same time, the existing desulfurization methods are costly, wasteful resources and low accuracy.

Method used

The method of synergistic catalysis and activation of hydrogen and water vapor is adopted to pretreat and follow-up treatment of activated carbon raw materials with high sulfur content to reduce sulfur residue, improve sulfur removal rate, and increase the specific surface area and mesoporosis of activated carbon.

Benefits of technology

The preparation of low-sulfur activated carbon was achieved, with sulfur content ≤230ppm, mesoporous proportion 50-70%, specific surface area 500-800m2/g, and total pore volume 0.4-0.6cm3/g, reducing production costs and hydrogen usage, and simplifying the Process flow.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004339815810000061
    Figure BDA0004339815810000061
Patent Text Reader

Abstract

The invention provides low-sulfur activated carbon and a preparation method thereof. The low-sulfur activated carbon meets the following conditions: the sulfur content is less than or equal to 230ppm, the mesopore proportion is 50-70%, the specific surface area is 500-800m < 2 > / g, the total pore volume is 0.4-0.6 cm < 3 > / g, and the mesopore volume is 0.2-0.4 cm < 3 > / g. The activated carbon with high sulfur content is used as a raw material, the residual quantity of sulfur in the activated carbon is synergistically reduced or the removal rate of sulfur impurities in the activated carbon is increased by adopting a synergistic catalysis and activation mode of hydrogen and water vapor, and meanwhile, compared with the prior art, the use amount of hydrogen is reduced, and the production cost is relatively low.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of preparation of activated carbon, and specifically relates to low-sulfur activated carbon and a preparation method thereof. Background Art

[0002] Activated carbon is a common carbon material, widely used in the fields of adsorption, separation, energy storage and catalysis, especially as a carrier of precious metal catalysts in various catalytic reactions. Commercially available activated carbon has a small specific surface area due to different sources, and is mostly microporous (pore size <2nm), containing only a small amount of mesoporous structure, which cannot meet the needs of different catalytic reactions. Accurately regulating the pore structure of activated carbon is a key technical issue in expanding the application of carbon materials. CN115520863A discloses a method for preparing coal-based activated carbon, which is mainly prepared by mixing coal powder, metal salt and solvent, and then subjecting to hydrothermal or solvothermal reaction and activation to obtain a specific surface area of ​​800-1300m 2 / g, mesopore volume 0.1-0.55cm 3 / g of coal-based activated carbon. Although this method increases the specific surface area and mesoporosity of the sample, it introduces transition metal salts such as iron salts, cobalt salts or nickel salts into the system, which not only increases the cost of raw materials but also complicates the subsequent processing procedures.

[0003] In addition, most activated carbon carbonization materials contain impurity sulfur. If no special treatment is done, it is difficult to use it as a carrier for a supported precious metal catalyst. The presence of impurity sulfur can cause poisoning and deactivation of precious metal catalysts (An investigation on Pd / C industrial catalysts for the purification of terephthalic acid. Catalysis Today, 44 (1998), 129-135.). Taking wood activated carbon as an example, it can be selected from high-quality sawdust, wood blocks, coconut shells, fruit shells, etc. Due to the different sources and origins of activated carbon raw materials, the content of impurity sulfur in the subsequent carbonization and activation process of manufacturing activated carbon is greatly affected by the activation process. Patent CN102190297B discloses a method for preparing activated carbon with low sulfur content, which mainly uses hydrogen as a desulfurizing agent, plant or mineral activated carbon as a raw material, and desulfurizes activated carbon for 1-20 hours at a temperature of 700-1000°C, normal pressure, and a molar ratio of hydrogen to activated carbon of 1:50-250. The sulfur content in the activated carbon can be as low as ≤50ppm. This technology uses a large amount of hydrogen, resulting in a waste of resources. In addition, the temperature required for sulfur removal is high and the desulfurization accuracy is low. Summary of the invention

[0004] In view of the problems existing in the prior art, the present invention provides a low-sulfur activated carbon and a preparation method thereof, which overcomes the problems of high sulfur content and small mesopore volume of the activated carbon, and the preparation method is simple and low-cost.

[0005] In a first aspect, the present invention provides a low-sulfur activated carbon, wherein the low-sulfur activated carbon satisfies the following conditions:

[0006] Sulfur content ≤ 230ppm, mesopore ratio 50-70%, specific surface area 500-800m 2 / g, total pore volume is 0.4~0.6cm 3 / g, the mesopore volume is 0.2~0.4cm 3 / g.

[0007] In a second aspect, the present invention provides a method for preparing low-sulfur activated carbon, comprising the following steps:

[0008] S1, pretreating the activated carbon raw material under a hydrogen atmosphere to obtain a pretreated activated carbon raw material;

[0009] S2. Treating the pretreated activated carbon raw material in a mixed atmosphere of hydrogen and water vapor.

[0010] In some embodiments, the sulfur content of the activated carbon raw material is greater than 100ppm, such as 100-500ppm, preferably greater than 300ppm, such as preferably 300-500ppm. For example, the sulfur content of the activated carbon raw material can be 110ppm, 150ppm, 200ppm, 250ppm, 300ppm, 330ppm, 360ppm, 380ppm, 410ppm, 440ppm, 470ppm or 500ppm. The present invention is applicable to the desulfurization of high sulfur content activated carbon raw materials.

[0011] In some embodiments, the activated carbon raw material is a carbonized material of wood or fruit shells; preferably, the activated carbon raw material is a carbonized material of fruit shells. The present invention has no particular limitation on the activated carbon to be desulfurized. Currently, activated carbon materials of wood or fruit shells can be used, and both can achieve good technical effects.

[0012] In some embodiments, the activated carbon raw material is coconut shell based activated carbon.

[0013] In some embodiments, the pretreatment temperature is 350-550°C, for example, 350°C, 380°C, 410°C, 450°C, 470°C, 500°C, 530°C, or 550°C.

[0014] In some embodiments, the pretreatment time is 0.5 to 3 h, for example, 0.5 h, 1 h, 1.5 h, 2 h, 2.5 h or 3 h.

[0015] In some embodiments, the pretreatment temperature is 400-500°C, for example, 400°C, 420°C, 440°C, 460°C, 480°C or 500°C.

[0016] In some embodiments, the pretreatment time is 1 to 2 hours, for example, 1 hour, 1.2 hours, 1.4 hours, 1.6 hours, 1.8 hours or 2 hours.

[0017] In some embodiments, in step S2, the treatment temperature is 700-900°C, for example, 700°C, 730°C, 780°C, 820°C, 850°C, 880°C or 900°C.

[0018] In some embodiments, the treatment time is 0.5 to 6 hours, for example, 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, or 6 hours.

[0019] In some embodiments, in step S2, the treatment temperature is 750-850°C, for example, 750°C, 780°C, 800°C, 820°C or 850°C.

[0020] In some embodiments, the treatment time is 1 to 3 hours.

[0021] In some embodiments, the sulfur content in the low-sulfur activated carbon is ≤230 ppm, preferably 50-230 ppm, for example, 50 ppm, 80 ppm, 130 ppm, 150 ppm, 180 ppm, 200 ppm or 230 ppm.

[0022] In some embodiments, the specific surface area of ​​the low-sulfur activated carbon is 500 to 800 m 2 / g, for example 500m 2 / g, 530m 2 / g, 550m 2 / g, 570m 2 / g, 590m 2 / g, 610m 2 / g, 640m 2 / g, 680m 2 / g, 720m 2 / g, 760m 2 / g or 800m 2 / g.

[0023] In some embodiments, the total pore volume of the low-sulfur activated carbon is 0.4 to 0.6 cm 3 / g, for example 0.415cm 3 / g, 0.455cm 3 / g, 0.489cm 3 / g, 0.518cm 3 / g, 0.559cm 3 / g or 0.592cm 3 / g.

[0024] In some embodiments, the mesopore volume of the low-sulfur activated carbon is 0.2 to 0.4 cm 3 / g, for example 0.211cm 3 / g, 0.256cm 3 / g, 0.351cm 3 / g or 0.389cm 3 / g.

[0025] In some embodiments, the mesopore ratio of the low-sulfur activated carbon is 50-70%, for example, 51%, 53%, 57%, 61%, 64% or 68%.

[0026] In some embodiments, during the pretreatment, the volume space velocity of hydrogen is 10 to 30 h -1 ; For example, 10h -1 , 15h -1 , 20h -1 , 25h -1 or 30h -1 .

[0027] In some embodiments, the volume space velocity of the water vapor is 5 to 20 h -1 , for example, 5h -1 , 8h -1 , 13h -1 , 16h -1 or 20h -1 .

[0028] The present invention uses activated carbon with a high sulfur content as a raw material, and adopts a synergistic catalysis and activation method of hydrogen and water vapor, which synergistically reduces the residual sulfur in the activated carbon, or improves the removal rate of sulfur impurities in the activated carbon. At the same time, compared with the prior art, the amount of hydrogen used is reduced, and the production cost is low. Specifically, pretreatment is first carried out in a hydrogen environment at a suitable temperature, and then water vapor is introduced to achieve sulfur removal at a lower temperature, while effectively increasing the surface area, total pore volume and mesoporosity of the sample. Compared with the prior art, the activated carbon treatment process described in the present invention is simple, only requires reducing gas hydrogen and green solvent water, and does not need to introduce other chemical reagents. The production cost is low, which is conducive to the subsequent large-scale processing of activated carbon. DETAILED DESCRIPTION

[0029] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiments. The specific embodiments described herein are only used to explain the present invention and are not intended to constitute any limitation of the present invention. In addition, in the following description, the description of known structures and technologies is omitted to avoid unnecessary confusion of the concepts of the present disclosure. Such structures and technologies are also described in many publications.

[0030] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0031] The present invention will be described in detail below through examples.

[0032] The specific surface area and pore structure of activated carbon were measured by nitrogen physical adsorption;

[0033] The sulfur content of activated carbon was measured by ICP-AES.

[0034] The radius of the pore structure of the activated carbon in the present invention is 2 to 50 nm.

[0035] Example 1

[0036] Weigh 30 g of coconut shell-based activated carbon and put it into a tubular furnace for pretreatment under a hydrogen atmosphere. The pretreatment conditions are a hydrogen atmosphere with a volume space velocity of 20 h -1 , 450℃ constant temperature for 1h; then steam treatment was carried out at the same time, and the steam treatment condition was a volume space velocity of 10h -1 , 700℃ for 2h, and naturally cooled to room temperature to obtain low-sulfur activated carbon. The structural parameters of the obtained low-sulfur activated carbon are shown in Table 1.

[0037] Example 2

[0038] Weigh 30 g of coconut shell-based activated carbon and put it into a tubular furnace for pretreatment under a hydrogen atmosphere. The pretreatment condition is a hydrogen volume space velocity of 20 h -1 , 450℃ constant temperature for 1h; then steam treatment was carried out at the same time, and the steam treatment condition was flow rate for 10h -1 , 750℃ for 2h, and naturally cooled to room temperature to obtain low-sulfur activated carbon. The structural parameters of the obtained low-sulfur activated carbon are shown in Table 1.

[0039] Example 3

[0040] Weigh 30 g of coconut shell-based activated carbon and put it into a tubular furnace for pretreatment under a hydrogen atmosphere. The pretreatment condition is a hydrogen volume space velocity of 20 h -1 , 450℃ constant temperature for 1h; then steam treatment was carried out at the same time, and the steam treatment condition was a volume space velocity of 10h -1 , 800℃ for 2h, and naturally cooled to room temperature to obtain low-sulfur activated carbon. The structural parameters of the obtained low-sulfur activated carbon are shown in Table 1.

[0041] Example 4

[0042] Weigh 30 g of coconut shell-based activated carbon and put it into a tubular furnace for pretreatment under a hydrogen atmosphere. The pretreatment condition is a hydrogen volume space velocity of 20 h -1 , 450℃ constant temperature for 1h; then steam treatment was carried out at the same time, and the steam treatment condition was a volume space velocity of 10h -1 , 850℃ for 2h, and naturally cooled to room temperature to obtain low-sulfur activated carbon. The structural parameters of the obtained low-sulfur activated carbon are shown in Table 1.

[0043] Example 5

[0044] Weigh 30 g of coconut shell-based activated carbon and put it into a tubular furnace for pretreatment under a hydrogen atmosphere. The pretreatment condition is a hydrogen volume space velocity of 20 h -1 , 450℃ constant temperature for 1h; then steam treatment was carried out at the same time, and the steam treatment condition was a volume space velocity of 10h -1 , 900℃ for 2h, and naturally cooled to room temperature to obtain low-sulfur activated carbon. The structural parameters of the obtained low-sulfur activated carbon are shown in Table 1.

[0045] Example 6

[0046] Weigh 30 g of coconut shell-based activated carbon and put it into a tubular furnace for pretreatment under a hydrogen atmosphere. The pretreatment condition is a hydrogen volume space velocity of 20 h -1 , 450℃ constant temperature for 1h; then steam treatment was carried out at the same time, and the steam treatment condition was a volume space velocity of 10h -1 , 700℃ for 1h, and naturally cooled to room temperature to obtain low-sulfur activated carbon. The structural parameters of the obtained low-sulfur activated carbon are shown in Table 1.

[0047] Example 7

[0048] Weigh 30 g of coconut shell-based activated carbon and put it into a tubular furnace for pretreatment under a hydrogen atmosphere. The pretreatment condition is a hydrogen volume space velocity of 20 h -1 , 450℃ constant temperature for 1h; then steam treatment was carried out at the same time, and the steam treatment condition was a volume space velocity of 10h -1 , 800℃ for 1h, and naturally cooled to room temperature to obtain low-sulfur activated carbon. The structural parameters of the obtained low-sulfur activated carbon are shown in Table 1.

[0049] Example 8

[0050] Weigh 30 g of coconut shell-based activated carbon and put it into a tubular furnace for pretreatment under a hydrogen atmosphere. The pretreatment condition is a hydrogen volume space velocity of 20 h -1 , 450℃ constant temperature for 1h; then steam treatment was carried out at the same time, and the steam treatment condition was a volume space velocity of 10h -1 , 900℃ for 1h, and naturally cooled to room temperature to obtain low-sulfur activated carbon. The structural parameters of the obtained low-sulfur activated carbon are shown in Table 1.

[0051] Example 9

[0052] Weigh 30 g of coconut shell-based activated carbon and put it into a tubular furnace for pretreatment under a hydrogen atmosphere. The pretreatment condition is a hydrogen volume space velocity of 20 h -1 , 450℃ constant temperature for 1h; then steam treatment was carried out at the same time, and the steam treatment condition was a volume space velocity of 10h -1 , 900℃ for 5h, and naturally cooled to room temperature to obtain low-sulfur activated carbon. The structural parameters of the obtained low-sulfur activated carbon are shown in Table 1.

[0053] Example 10

[0054] Weigh 30 g of coconut shell-based activated carbon and put it into a tubular furnace for pretreatment under a hydrogen atmosphere. The pretreatment condition is a hydrogen volume space velocity of 20 h -1 , 850℃ constant temperature for 1h; then steam treatment was carried out at the same time, and the steam treatment condition was a volume space velocity of 10h -1 , 850℃ for 1h, and naturally cooled to room temperature to obtain low-sulfur activated carbon. The structural parameters of the obtained low-sulfur activated carbon are shown in Table 1.

[0055] Comparative Example 1

[0056] The treatment process of activated carbon is the same as the preparation process of Example 10, except for hydrogen pretreatment and no steam treatment. Specifically, 30 g of coconut shell-based activated carbon was weighed and placed in a tubular furnace and treated under a hydrogen atmosphere at a hydrogen volume space velocity of 20 h -1 , 850℃ constant temperature for 2h, and naturally cooled to room temperature to obtain low-sulfur activated carbon. The structural parameters of the obtained low-sulfur activated carbon are shown in Table 1.

[0057] Comparative Example 2

[0058] The treatment process of activated carbon is the same as the preparation process of Example 10, except that there is no hydrogen pre-treatment in the system, only water vapor treatment. Specifically, 30 grams of coconut shell-based activated carbon is weighed and placed in a tubular furnace, and treated with water vapor at a water vapor volume space velocity of 10 h -1 , 850℃ constant temperature for 2h, and naturally cooled to room temperature to obtain low-sulfur activated carbon. The structural parameters of the obtained low-sulfur activated carbon are shown in Table 1.

[0059] Comparative Example 3

[0060] The treatment process of activated carbon is the same as the preparation process of Example 10, except that hydrogen and water vapor are used to treat the activated carbon simultaneously in the pretreatment stage. Specifically, 30 grams of coconut shell-based activated carbon is weighed and placed in a tubular furnace. In a hydrogen and water vapor atmosphere, the hydrogen volume space velocity is 20h / min. -1 , water vapor volume space velocity 10h -1 , 850℃ constant temperature for 2h, and naturally cooled to room temperature to obtain low-sulfur activated carbon. The structural parameters of the obtained low-sulfur activated carbon are shown in Table 1.

[0061] Comparative Example 4

[0062] The treatment process of activated carbon is the same as the preparation process of Example 10, except that the order of hydrogen and water vapor treatment is changed. Specifically, 30 grams of coconut shell-based activated carbon is weighed and placed in a tubular furnace for water vapor treatment. The water vapor volume space velocity is 10h -1 , 850℃ constant temperature for 1h, then hydrogen treatment, hydrogen volume space velocity 20h -1 , and then the temperature was kept at 850℃ for 1 hour, and then naturally cooled to room temperature to obtain low-sulfur activated carbon. The structural parameters of the obtained low-sulfur activated carbon are shown in Table 1.

[0063] Table 1

[0064]

[0065] Examples 1-5 further verify the effect of treatment temperature on the desulfurization rate by changing the treatment temperature of coconut shell-based activated carbon in a mixed atmosphere of hydrogen and water vapor. As can be seen from Table 1, with the increase of treatment temperature, the desulfurization rate gradually increases, but when the treatment temperature is higher than 850°C, the mesopore ratio decreases. Examples 6-9 show that the longer the treatment time, the higher the desulfurization rate. Compared with Example 1, Example 10 shows that too high a pretreatment temperature will reduce the desulfurization rate.

[0066] In Comparative Example 1, only hydrogen pretreatment was performed, and no water vapor treatment was performed. When the hydrogen volume space velocity in Comparative Example 1 was the same as that in Example 4, the desulfurization rate was significantly reduced, further illustrating that the present application uses hydrogen and water vapor for synergistic catalysis and activation, which can reduce the amount of hydrogen used, increase the desulfurization rate, and reduce costs.

[0067] In summary, compared with the comparative examples, it can be seen that the present invention uses activated carbon with a high sulfur content as a raw material, and adopts hydrogen and water vapor for synergistic catalysis and activation, which synergistically reduces the residual sulfur in the activated carbon, or increases the removal rate of sulfur impurities in the activated carbon. At the same time, compared with the prior art, the amount of hydrogen used is reduced, and the production cost is low. Specifically, firstly, pretreatment is carried out in a hydrogen environment at a suitable temperature, and then water vapor is introduced to achieve sulfur removal at a higher temperature, while effectively increasing the surface area, total pore volume and mesoporosity of the sample. Compared with the prior art, the activated carbon treatment process described in the present invention is simple, requiring only reducing gas hydrogen and green solvent water, without the introduction of other chemical reagents, and has a low production cost, which is conducive to the subsequent large-scale processing of activated carbon.

[0068] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A low-sulfur activated carbon, wherein: The low-sulfur activated carbon meets the following conditions: Sulfur content ≤ 230ppm, mesopore ratio 50-70%, specific surface area 500-800m 2 / g, total pore volume is 0.4~0.6cm 3 / g, the mesopore volume is 0.2~0.4cm 3 / g.

2. A method for preparing low-sulfur activated carbon, comprising the following steps: S1, pretreating the activated carbon raw material under a hydrogen atmosphere to obtain a pretreated activated carbon raw material; S2. Treating the pretreated activated carbon raw material in a mixed atmosphere of hydrogen and water vapor.

3. The preparation method according to claim 2, characterized in that: The sulfur content of the activated carbon raw material is greater than 100 ppm, such as 100 to 500 ppm, preferably greater than 300 ppm, such as preferably 300 to 500 ppm.

4. The preparation method according to claim 2, characterized in that: The activated carbon raw material is wood or fruit shell carbonized material; Preferably, the activated carbon raw material is a carbonized fruit shell material; Preferably, the activated carbon raw material is coconut shell based activated carbon.

5. The preparation method according to any one of claims 2 to 4, characterized in that: The pretreatment temperature is 350-550° C., and the pretreatment time is 0.5-3 h.

6. The preparation method according to any one of claims 2 to 5, characterized in that: The pretreatment temperature is 400-500° C., and the pretreatment time is 1-2 hours.

7. The preparation method according to any one of claims 2 to 6, characterized in that: In step S2, the treatment temperature is 700-900°C, and the treatment time is 0.5-6h.

8. The preparation method according to any one of claims 2 to 7, characterized in that: In step S2, the treatment temperature is 750-850°C, and the treatment time is 1-3 hours.

9. The preparation method according to any one of claims 2 to 8, characterized in that: The sulfur content of the low-sulfur activated carbon is ≤230 ppm, preferably 50 to 230 ppm, and / or The specific surface area of ​​the low-sulfur activated carbon is 500 to 800 m 2 / g, the total pore volume of the low-sulfur activated carbon is 0.4 to 0.6 cm 3 / g, the mesopore volume of the low-sulfur activated carbon is 0.2-0.4cm 3 / g, and the mesopore ratio of the low-sulfur activated carbon is 50-70%.

10. The preparation method according to any one of claims 2 to 8, characterized in that: During the pretreatment process, the hydrogen volume space velocity is 10 to 30 h -1 ; and / or The volume space velocity of the water vapor is 5 to 20 h -1 .

Citation Information

Patent Citations

  • Preparation method of activated carbon with low sulphur content

    CN102190297B

  • Coal-based activated carbon prepared by hydrothermal or solvothermal method as well as preparation method and application of coal-based activated carbon

    CN115520863A

  • Preparation method of activated carbon with low sulphur content

    CN102190297A

  • Desulphurization method of carbonized materials

    CN102464317A

  • Purification of petroleum coke

    GB1299572A